English and empire literary history, dialect, and the digital archive - Brown, David West (Studies in English languages, 2018)
"'English and Empire: literary history, dialect, and the digital archive' combining statistical modelling and archival study, investigates how African diasporic, Chinese, and Indian characters have been voiced in British fiction and drama produced between 1768 and 1929. The analysis connects patterns of linguistic representation to changes in the imperial political economy, to evolving language ideologies that circulate in the Anglophone world, and to shifts in sociocultural anxieties that crosscut race and empire. In carrying out his investigation, David West Brown makes the case for a methodological approach that links the distant (quantitative) and close (qualitative) reading of diverse digital artefacts. Taking an interdisciplinary approach, the book will appeal to a variety of scholars and students including sociolinguists interested in historical language variation, as well as literary scholars interested in postcolonial studies and the digital humanities"